2020
DOI: 10.1177/1071100720922220
|View full text |Cite
|
Sign up to set email alerts
|

A Consensus Statement on the Surgical Treatment of Charcot-Marie-Tooth Disease

Abstract: Background: Charcot-Marie-Tooth (CMT) disease is a hereditary motor-sensory neuropathy that is often associated with a cavovarus foot deformity. Limited evidence exists for the orthopedic management of these patients. Our goal was to develop consensus guidelines based upon the clinical experiences and practices of an expert group of foot and ankle surgeons. Methods: Thirteen experienced, board-certified or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(52 citation statements)
references
References 34 publications
(33 reference statements)
0
41
0
Order By: Relevance
“…The majority of patients were male (18/25, 72%) and had CMT1A due to chromosome 17 duplication (17/25, 68%). The mean CMTES v2 was 11 (SD 4.5) (range [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of patients were male (18/25, 72%) and had CMT1A due to chromosome 17 duplication (17/25, 68%). The mean CMTES v2 was 11 (SD 4.5) (range [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19].…”
Section: Resultsmentioning
confidence: 99%
“…More recently, a consensus on the surgical management of cavovarus foot in CMT patients was reached by a large group of American foot and ankle surgeons. 11 The aim of this study was to evaluate longitudinally the effect of foot surgery in a cohort of CMT patients.…”
Section: Introductionmentioning
confidence: 99%
“…19,30 Surgeons recommend early interventions to guarantee a proper and balanced strengthening of the foot-leg region. 25,28,29,31 However, before surgery it is important to inform patients about potential relapses. Since FS strives to preserve foot flexibility, the results could be undermined due to progressive characteristics of the underlying neurological condition and to joint structural changes.…”
Section: Discussionmentioning
confidence: 99%
“…Healthcare professionals should know that patient engagement represents a very sensitive moment. 31 During the initial examination, the medical staff welcomes any requests and personal expectations brought forth by patients, carefully evaluating all functional clinical cues, and eventually formulating a potential scenario for a surgical and postsurgical tailored program that has to be thoroughly discussed with the patient. From recent literature we know that informing and engaging a subject can be a way to make them an integral part of their healing process, therefore, improving their satisfaction level following surgery.…”
Section: Discussionmentioning
confidence: 99%
“…A survey on current practice revealed that there were differences in the approaches between different centres and countries [ 37 ]. During the last few years, commendable efforts have been devoted to compare experiences and reach consensus on which procedures should be done and which should be avoided [ 38 , 39 ]. Surgery, if indicated ideally after multidisciplinary evaluation and in the hands of an orthopaedic surgeon with expertise in CMT, should occur early, as fixed deformities are more difficult to treat, in an individualised manner and according to determined sequences of procedures.…”
Section: Current Managementmentioning
confidence: 99%